Analytical modeling and experimental validation of micro end-milling cutting forces considering edge radius and material strengthening effects. (October 2015) - Zhou, L.; Peng, F.Y.; Yan, R.; Yao, P.F.; Yang, C.C.; Li, B.
Abstract: This paper presents a novel micro end-milling cutting forces prediction methodology including the edge radius, material strengthening, varying sliding friction coefficient and run-out together. A new iterative algorithm is proposed to evaluate the effective rake angle, shear angle and friction angle, which takes into account the effects of edge radius as well as varying sliding friction coefficient. A modified Johnson–Cook constitutive model is introduced to estimate the shear flow stress. This model considers not only the strain-hardening, strain-rate and temperature but also the material strengthening. Furthermore, a generalized algorithm is presented to calculate uncut chip thickness considering run-out. The cutting forces model is calibrated and validated by NAK80 steel, and the relevant micro slot end-milling experiments are carried out on a 3-axis ultra-precision micro-milling machine. The comparison of the predicted and measured cutting forces shows that the proposed model can provide very accurate predicted results. Finally, the effects of material strengthening, edge radius and cutting speed on the cutting forces are investigated by the proposed model and some conclusions are given as follows: (1) the material strengthening behavior has significant effect on micro end-milling process at the micron level. (2) Cutting forces predicted increase with the increase of edge radius. (3) Considering varying sliding friction coefficient can enhance the sensitivity of the predicted cutting forces to cutting speed. Highlights: A novel micro end-milling cutting forces prediction methodology was presented. Edge radius, material strengthening and sliding friction coefficient were considered. Material strengthening has a significant effect on cutting forces at micron level. Cutting forces predicted increase with the increase of edge radius. Varying sliding friction coefficient affects the predicted cutting forces.